Theory of change : debates and applications to access and participation in higher education - Dent, Samuel; Mountford-Zimdars, Anna; Burke, Ciaran (Great debates in higher education., 2022)
Theory of Change speaks to those looking for an academically rigorous discussion of the origins and debates around this approach in Higher Education. Melding together robust academic research with examples of practice, the book provides specific applications of using a Theory of Change across key stages of the student life cycle. The Theory of Change underpinning this book is that national and international practitioners, policy makers, higher education professionals, students and academic faculty will increase awareness and ability to use a Theory of Change in their own work. This, in turn, will mainstream the use which will lead to better interventions and practices. In the field of access and participation in higher education, it will ultimately lead to more disadvantaged students entering and successfully progressing from higher education. This book helps to establish a common lexicon around a Theory of Change approach and enable discussion of demonstrable, meaningful reflections on the 'change' work has on inequalities in higher education access and participation.